O nascimento de um mestre do grotesco: Gastão Cruls (Revista de Crítica Literaria Latinoamericana, 2025)
This paper aims at a critical reading of Gastão Cruls’ unpublished short story, “O seio de Rosaura [The Breast of Rosaura].” Written between 1910 and 1917, therefore before his first publications, it narrates the story of a young man suffering from tertian fever, who is haunted by the image of the combination of the body of his beloved Rosaura with the body of an old man deformed by aggressive cancer, and anticipates the main characteristics of Cruls’ later fiction: (i) grotesque themes that defy understanding; (ii) disillusionment with science, which explores the concerns about the limits and the risks inherent to knowledge; (iii) the horrors associated with our irremediable biological condition, in particular, our libido, whose phobic potential was explored by many great works at the turn of the century: Robert Louis Stevenson’s Strange Case of Dr. Jekyll and Mr. Hyde (1886); Arthur Machen’s The Great God Pan (1894); Bram Stoker’s Dracula (1897), just to mention a few ones.
Keywords: Brazilian Literature; Gothic; Gastão Cruls